A warmer and greener cold world: summer warming increases shrub growth in the alpine and high Arctic tundra - Weijers, Setf; Meyers-Smith, Isla H.; Löffler, Jörg (ERDKUNDE, 2018)
The Arctic and alpine biome is rapidly warming, which might be causing an encroachment of relatively tall woody shrub vegetation into tundra ecosystems, which will probably result in an overall positive feedback to climate warming. This encroachment is, however, believed to remain limited to the relatively warm parts of the biome, where taller shrubs may displace shorter species. Still, climate sensitivity of shrub growth strongly differs between species and sites and High Arctic dwarf shrub species may respond rapidly to increasing temperatures in absence of taller species. In addition, it remains largely unknown whether shrubs from different functional groups from the same sites respond similarly to climate drivers. In the present study we examined the climate-growth relationships of six different site-species combinations: one evergreen and one deciduous shrub species at two alpine sites, and one evergreen dwarf shrub species at two High Arctic sites. We compared linear mixed models for each combination, explaining existing shrub growth data with site-specific interpolated monthly and seasonal climate data from the gridded meteorological dataset CRU TS4.00. Shrub growth rates were found to be sensitive to summer climate for all species at all sites. Continued and projected warming is thus likely to stimulate a further encroachment of shrubs in these systems, at least through a densification of existing stands. Dwarf shrub growth strongly responded to the recent warming at both High Arctic sites, contrasting with previous work suggesting that shrub expansion might remain limited to warmer tundra regions. At the alpine sites, growth of evergreen shrubs was found to be more dependent on summer climate than growth of deciduous shrubs, perhaps because these evergreen species are less prone to herbivory. However, biome-wide generalizations at the functional group level may be difficult to interpolate to the species level. Micro-site conditions, such as the determination of growing season length and winter soil temperatures, and influence on growing season soil moisture by snow depth, may determine the strength of the climate-growth relationships found.